Contribution to the research of oscillatory loads of sprung and unsprung masses in order to create conditions for laboratory tests of heavy motor vehicles - Demić, Miroslav D.; Đurić, Aleksandar S.; Grkić, Aleksandar R.; Drakulić, Momir M.; Muždeka, Slavko (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: Motor vehicles are complex dynamic systems due to spatial displacements, changes in the characteristics of components during their lifetime, a large number of influences and disturbances, the appearance of backlash, friction, hysteresis, etc. The aforementioned dynamic phenomena, especially vibrations, cause driver and passenger fatigue, reduce the lifetime of the vehicle and its systems, etc.Methods: In general, the movement of vehicles is carried out on uneven roads and curvilinear paths in the road. Not only do oscillatory movements cause material fatigue of vehicle parts, but they also have a negative effect on people's health. That is why special attention must be paid to the coordination of the mutual movement of the subsystems, and in particular, the vehicle suspension system, even at the stage of the motor vehicle design. For these purposes, theoretical, experimental or combined methods can be used. Therefore, it is very useful to have the experimental results of the oscillations of the vehicle subsystem in operating conditions, so the aim of this work was to use the movement of the 4x4 drive FAP 1118 vehicle in operating conditions (due to higher speeds - in road conditions) to define the conditions for testing oscillatory loads in laboratory conditions. Results:This is made possible by registering and identifying statistical parameters of registered quantities.Conclusion: Based on the measured data, the research can be programmed on shakers in laboratory conditions, and, at the same time,  the size to be reproduced can be chosen as well.
Keywords: motor vehicle; sprung and unsprung masses; oscillatory loads; laboratory tests